Motilitas dan Keutuhan Membran Plasma Spermatozoa Ayam Kampung yang Disimpan dengan Penurunan Suhu yang Berbeda: Motility and Plasma Membrane Integrity of Kampung Chicken Spermatozoa of Stored with Different Temperature Decreasing - Khaeruddin, Khaeruddin (Anoa: Journal of Animal Husbandry, 2023)
Semen storage at a temperature of 50C affects the quality of spermatozoa. The purpose of this study was to determine the differences in motility and plasma membrane integrity of Kampung chicken spermatozoa variables that were stored directly at 5 °C with storage with a gradual decrease in temperature after the semen collection process. This study used a completely randomized design with 3 treatment levels and 9 replications. The treatment used was storage at a fixed temperature of 5 ⁰C for 75 minutes (P1), storage at a gradually lowered temperature from 41 ⁰C 30 minutes - 21 ⁰C 30 minutes - 5 ⁰C 15 minutes (P2), and storage at a gradually lowered temperature from temperature 41⁰C 15 minutes - 31 ⁰C 15 minutes - 21 ⁰C 15 minutes - 11 ⁰C 15 minutes - 5 ⁰C 15 minutes (P3). Research data that were normally distributed were analyzed using analysis of variance (ANOVA). The results showed that different temperature reduction treatments did not affect (P>0.05) the motility and plasma membrane integrity of spermatozoa variables during storage. The mean total motility, progressive motility and plasma membrane integrity were 25.36-41.22%, 67.30-77.08% and 92.35-96.29%, respectively. The conclusion of this study was that collected Kampung chicken spermatozoa could be directly stored at 5°C without any gradual reduction in temperature because no differences in plasma membrane integrity motility variables were found in the treatment.